Perfringolysin O Expression in Clostridium perfringens Is Independent of the Upstream pfoR Gene - Awad, Milena M. (American Society for Microbiology, 2002)
The pathogenesis of Clostridium perfringens-mediated gas gangrene or clostridial myonecrosis involves the extracellular toxins alpha-toxin and perfringolysin O. Previous studies (T. Shimizu, A. Okabe, J. Minami, and H. Hayashi, Infect. Immun. 59:137-142, 1991) carried out with Escherichia coli suggested that the perfringolysin O structural gene, pfoA, was positively regulated by the product of the upstream pfoR gene. In an attempt to confirm this hypothesis in C. perfringens, a pfoR-pfoA deletion mutant was complemented with isogenic pfoA(+) shuttle plasmids that varied only in their ability to encode an intact pfoR gene. No difference in the ability to produce perfringolysin O was observed for C. perfringens strains carrying these plasmids. In addition, chromosomal pfoR mutants were constructed by homologous recombination in C. perfringens. Again no difference in perfringolysin O activity was observed. Since it was not possible to alter perfringolysin O expression by mutation of pfoR, it was concluded that the pfoR gene product is unlikely to have a role in the regulation of pfoA expression in C. perfringens.